Conceptual metaphors in proverbs: Conduits of cultural values and beliefs - Issa, Muhammad; Ali, Shumaila Shafket (Yayasan Mitra Persada Nusantara, 2025)
This study explores the similarities and differences in conceptual metaphors found in the proverbs of two indigenous languages, Balti and Burushaski, spoken in Gilgit-Baltistan, Pakistan. Focusing on metaphors related to animals, birds, fruits, and vegetables, the study analyzes 20 proverbs from each language. Data were collected from native speakers familiar with the proverbs and from two published books on the proverbs of Balti and Burushaski. The research employs the Conceptual Metaphor Theory (CMT) to analyze how these metaphors reflect the values and worldview of the respective speech communities. Through qualitative comparative analysis, the study reveals insights into the cultural and linguistic differences and similarities between the two communities. The findings highlight how metaphors encapsulate beliefs and attitudes towards various aspects of life, providing a deeper understanding of the cultural perspectives of both groups. This research contributes to the fields of cross-cultural linguistics and paremiology, offering valuable insights into the preservation and promotion of heritage languages and cultures. By exploring these indigenous proverbs, the study emphasizes the significance of understanding cultural diversity and the importance of safeguarding indigenous languages.